Pengaruh Komunikasi dan Motivasi Kerja terhadap Disiplin Kerja Pegawai pada Kantor Kecamatan Bontang Utara - Agusyani; Murti, Salsabina Rudi; Ramadhani, Nur Padillah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study aims to determine how the work discipline of employees at the North Bontang District Office is influenced by motivation and communication. The subjects of this study were 59 workers in the North Bontang sub-district office who could provide related data for analysis. With SPSS 16.0, correlation analysis is used to collect data. This study used a quantitative approach, data collection through questionnaires, interviews, documentation, literature studies, and observations. The data were analyzed using multiple linear regression tests, hypothesis testing, data quality tests, and classical assumption tests. The results showed, partially work discipline (Y) was significantly influenced by the communication variable (X1) and significantly influenced by the work motivation variable (X2). Simultaneously, employee discipline (Y) at the North Bontang sub-district office is positively and significantly influenced by work motivation (X2) and communication (X1). Thus, the results of this study show that communication and work motivation between employees at the North Bontang sub-district office have an effect on improving work discipline.